Digitalização, sustentabilidade e inovação inclusiva na Europa rural: oportunidades e desafios para o setor agroalimentar - Tartaruga, Iván Gerardo Peyré (2021)
This text aims to examine the importance of digitization in European rural spaces in recent years, especially in the agri-food sector. At the same time, it is intended to stress the implications for sustainability, as a central theme in the current debate on technological changes. Furthermore, this research provides an exploratory scenario, of rural Europe, of the regions that present a greater potential for the application and generation of digital innovations in agrifood and those that have a greater difficulty in innovating. In both cases, such regions will be a combination of challenges and opportunities for territorial development. To fulfill these purposes, a literature review was carried out on the contributions of digitization to agri-food and rural territories in the European Union, and a spatial analysis of economic, environmental, digitization and inclusion data (Eurostat platform) was executed for the year 2017 and for regions (NUTS 2) and countries. The results indicate the important role of the main community policies in recent years related, directly or indirectly, to the agri-food sector, both in general terms - European Green Deal or Smart Specialization strategy - and in specific terms - "From Farm to Plate" strategies or Sustainable Agriculture. The most innovative and prosperous regions are spatially concentrated in clusters of innovation. In less developed regions there are a variety of growth trajectories that depend on state support for their achievement. In both regions, there are major challenges related to digitization, namely data ownership and control, data development and data security, which together shape the future of food and agriculture in the EU.